Right-of-way for transmission facilities as regulation of legal relationships regarding real estate between the real estate owner and the transmission entity - Przewięźlikowska, Anna (International Conference “Environmental Engineering”, 2017)
In Poland, after World War II, most of the technical infrastructure was built based on a construction permit, and without a legal title to a given real property. Therefore, a necessity arose for the regulation of property rights where technical infrastructure was built. For the establishment of the right-of-way for transmission facilities it is essential to regulate the legal relationships between the owner of the real estate and the transmission entity and their entry into the land and mortgage register. The extent of the granted right f ay determines the value of consideration for the owner of the encumbered property. This study analyzes the rules for the determination, establishment and surveying preparation of the right f a y for various types of transmission facilities. First a thorough examination of the legal status of the real property was re quired and then the extent of the necessary right f ay to be established for the given facilities was analyzed. The next stage of the study involved determining the extent of the rights f a y and appropriate protective zones for the networks pursuant to the relevant technical guidelines. The analysis revealed significant diversity of legal regulations on the establishment of the right-of-way for the specific types of public utilities.
Keywords: right-of-way for transmission facilities; public utilities; real property encumbrance